Current and future competitiveness of the Icelandic and Norwegian salmon farming industries: A comparison of economic performance, productivity, and characteristics of the national environments in which the salmon farming companies operate - Vormedal, Sverre (UiT The Arctic University of Norway, 2021)
While Norway has had a world-leading position in farmed Atlantic salmon since the pioneer age of the 1960s and 1970s, Iceland’s history of salmon farming is one of misadventure; however, a third attempt to become a viable player in the global industry is underway. Despite disagreements over terminology and the extent to which each country-specific characteristic affects the success of firms operating within it, economic and strategic management literature generally accepts that aspects of the national environment are explanatory variables when determining competitiveness This thesis aims to assess the prospects for success of the Icelandic salmon farming industry. Specifically, it aims to assess the industry´s current competitive situation, its potential development, and what country-specific differences are of most interest. Biologic and economic parameters are measured and compared with equivalent data points from Norway found in literature and official sources, using unique data collected from Icelandic salmon farming companies, including annual and generational bioeconomic variables. While current competitiveness is determined by relative cost and price achievement, future development in competitive positions is based on a theoretical and integrated understanding of the cost drivers, which are derived from a systematic and in-depth analysis of biological performance and labor efficiency, as well as the industry’s context. Norway is found to have significantly lower cost over the compared period, while Iceland generally achieves higher prices due to higher slaughter weight and possibly premium prices. Thus, and theoretically, Iceland’s current competitive position cannot be determined, whether it is one of competitive advantage or disadvantage. Additionally, it demonstrates that, under equal conditions, 40 percent of the cost difference can be accounted for by differences in labor productivity. The exponential growth rate and lag in production can account for some of this and these effects on labor ...